THE INFLUENCE OF PREVERBAL TRAUMA ON THE OCCURRENCE OF PROCRASTINATION IN HIGHER EDUCATION STUDENTS - Янченко, Олена; Іващенко, Альона (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article presents the results of a theoretical analysis of the phenomenon of ‘procrastination’ and an empirical study of the peculiarities of the influence of the level of preverbal trauma on the intensity of procrastination in higher education students. The aim of the study is to theoretically substantiate and empirically study the psychological characteristics of procrastination in higher education students. A substantive analysis of the concept of ‘procrastination’ in higher education students is carried out. It is stated that procrastination is largely an emotional reaction to planned or necessary tasks; it manifests itself in the fact that a person, being aware of the need to perform very specific important tasks, ignores this need and diverts his attention to everyday trifles or entertainment. The empirical study was conducted in June-July 2024 using a set of empirical methods: ‘K. Ley’s General Procrastination Scale to quantify the level of the subjects’ tendency to postpone their own tasks; M. Dvornik’s author’s methodology “Causes of Personal Tendency to Postpone Tasks” to find out the leading causes of procrastination and the fundamental difference between them; the questionnaire “Diagnosis of Verbal Trauma According to the Self-Reconstruction Psychotherapy Method” to determine the level of verbal trauma in the subjects. To process the data, the mathematical and statistical method was used: Pearson’s linear correlation coefficient r. The nature of the relationship between the level of procrastination and individual personality tendencies to postpone tasks is studied and described. It is found that the key reasons for procrastination are: a reduced level of interest, underestimation of readiness to perform, fear. The peculiarities of the influence of the level of preverbal trauma on the intensity of procrastination in higher education students are empirically investigated. Results: the existence of a relationship between the overall level of procrastination and verbal trauma is revealed. It is concluded that with an increase in the level of development of verbal trauma, the overall level of procrastination increases. In the current life situation, it is the work with awareness of the psychological processes that took place during the preverbal period of personality development that helps to reduce the overall level of anxiety, and therefore will affect the reduction of procrastination in higher education students in the performance of tasks.